Implementasi Pembelajaran Fiqih Melalui Kitab Klasik dalam melestarikan Budaya Pesantren di MA Model Zainul Hasan Genggong Probolinggo - khatijah khatijah; Moh. Ismail (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
The purpose of this study is to describe the implementation of Fiqh Learning through the Classical Book in preserving the Islamic Boarding School Culture at the Zainul Hasan Genggong MA Model Probolinggo. Through a qualitative approach, the results of this study indicate that the implementation of classical book-based Fiqh learning in the MA Model requires students to have the ability to understand the material contained in the classical book. In its implementation, educators use expository strategies. Educators also use bandongan, sorogan, lecture, question and answer methods, and discussion methods in understanding a problem